Ecological quality assessment of transitional waters based on fish assemblages in Portuguese estuaries: the Estuarine Fish Assessment Index (EFAI) - Cabral, H. N. (2017)
The assessment of water quality has changed markedly worldwide over the last years, especially in Europe due to the implementation of the Water Framework Directive. Fish was considered a key-element in this context and several fish-based multi-metric indices have been proposed. In this study, we propose a multimetric index, the Estuarine Fish Assessment Index (EFAI), developed for Portuguese estuaries, designed for the overall assessment of transitional waters, which could also be applied at the water body level within an estuary. The EFAI integrates seven metrics: species richness, percentage of marine migrants, number of species and abundance of estuarine resident species, number of species and abundance of piscivorous species, status of diadromous species, status of introduced species and status of disturbance sensitive species. Fish sampling surveys were conducted in 2006, 2009 and 2010, using beam trawl, in 13 estuarine systems along the Portuguese coast. Most of the metrics presented a high variability among the transitional systems surveyed. According to the EFAI values, Portuguese estuaries presented a “Good” water quality status (except the Douro in a particular year). The assessments in different years were generally concordant, with a few exceptions. The relationship between the EFAI and the Anthropogenic Pressure Index (API) was not significant, but a negative and significant correlation was registered between the EFAI and the expert judgement pressure index, at both estuary and water body level. The ordination analysis performed to evaluate similarities among North-East Atlantic Geographical Intercalibration Group (NEAGIG) fish-based indices put in evidence four main groups: the French index, since it is substantially different from all the other indices (uses only four metrics based on densities); indices from Ireland, United Kingdom and Spain (Astúrias and Cantábria); the Dutch and German indices; and the indices of Belgium, Portugal and Spain (Basque country). The need for detailed studies, including comparative approaches, on several aspects of these assessment tools, especially in what regards their response to anthropogenic pressures was stressed.